THE EFFECT OF THE BALANCING MOVEMENT PROGRAM USING THE MAGIC ANIMAL WAY ON THE BALANCE OF SCHOOL-AGE CHILDREN WITH PHYSICAL DISABILITIES - Kansri, Jaruwan; Samana-changpheuk , Prachaya; Booranarek, Sasiwimon (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2024)
The aim of this quasi-experimental study using a one-group pretest-posttest design was to determine the effect of the balancing movement program using Magic Animal Way on the balance of school-age children with physical disabilities in balancing movement. The sample group consisted of 20 school-age children with physical disabilities in balancing movement, aged between 7 and 12 years, from Chai Nat Special Education School in Mueang District, Chai Nat Province. They were selected based on specified qualification criteria. The research instrument was the balancing program "Magic Animal Way" and the Pediatric Balance Scale (PBS) assessment form. The content validity values (IOC) ranged from .94 to .98. The Cronbach’s alpha coefficient for the PBS questionnaire was .72. Data were analyzed using descriptive statistics, which are frequency, percentage, mean, and standard deviation. The dependent t-test was used to compare the PBS scores. The results of this study reveal that balancing scores in school-age children with physical disabilities in balancing movement improved after receiving the Magic Animal Way program, with statistical significance at the .05 level (M = 29.08, SD = 6.29 and M = 14.60, SD = 4.45, t = - 13.093, p = .000). The results recommend that this program should be utilized to improve the balance of school-age children with physical disabilities in balancing movement, enabling them to more effectively assist themselves.